Perubahan Motif Wisata Pada Era Industri 4.0 (Case study : Sam Poo Kong Temple, Semarang) - I D Murtadha Isnan; Pramesi Lokaprasidha (Journal of Tourism and Creativity, 2020)
Abstract The industrial revolution 4.0 is not only a technological development from the previous era, but it is also able to turn off conventional business. Internet connectivity that connects all parts of the world with just the touch of a finger on a smartphone is able to turn off the industry, one of which is conventional transportation services that exist today. The industrial revolution 4.0 will also bring the distance between producers and their target markets to a close relation. Digital marketing is a way to promote products/brands through internet. Through advertising on social media or e-commerce. In the world of tourism, motivation is one important factor for tourists in making decisions about tourist destinations to be visited. Tourists will have perceptions of possible tourist destinations, where these perceptions can be generated by individual preferences, prior experience, and information that can be obtained. The current motivation of tourists to Sam Poo Kong Temple has begun to change, which once had a religious motive but now has changed to a motive for social status. Sam Poo Kong temple which has spiritual and cultural values ​​especially for Confucians changes in line with the times in the millennial era. Orientation on the use of social media can change the visiting trend and support psychological needs in terms of popularity on social media pages. Keywords: Digital marketing, Tourist Motives, Revolusi industry 4.0, Sam Poo Kong Temple